Pengaruh Budaya Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai Negeri Sipil pada Kantor Balai Standardisasi dan Pelayanan Jasa Industri di Samarinda (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of work culture and job satisfaction on the performance of Civil Servants (PNS) at the Samarinda Office of Standardization and Industrial Services (BSPJI). The research method used is quantitative with a questionnaire distribution technique to 30 respondents. The results of multiple linear regression analysis indicate that work culture has a positive and significant effect on employee performance, while job satisfaction does not have a significant effect. Simultaneously, work culture and job satisfaction have a significant effect on employee performance. The coefficient of determination (Adjusted R²) value of 0.290 indicates that 29% of employee performance variables are influenced by culture and job satisfaction, while the rest are influenced by other factors. These findings underline the importance of implementing a strong work culture to improve performance, as well as the need for further evaluation of other factors that influence employee job satisfaction. This study provides theoretical contributions to the development of human resource management and practical implications for policy makers in government agencies